2021
DOI: 10.3390/life11040282
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclides Transfer from Soil to Tea Leaves and Estimation of Committed Effective Dose to the Bangladesh Populace

Abstract: Considering the probable health risks due to radioactivity input via drinking tea, the concentrations of 226Ra, 232Th,40K and 137Cs radionuclides in the soil and the corresponding tea leaves of a large tea plantation were measured using high purity germanium (HPGe) γ-ray spectrometry. Different layers of soil and fresh tea leaf samples were collected from the Udalia Tea Estate (UTE) in the Fatickchari area of Chittagong, Bangladesh. The mean concentrations (in Bq/kg) of radionuclides in the studied soil sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…Potassium has an important role in photosynthesis, translocation of starches and sugars, plant-water relations, protein synthesis, activation of plant enzymes, resistance to plant diseases [8,29]. Similar results were reported in the studies examining the herbaceous and woody plants [7,15,27]. Manigandan et al [3] reported the 40K activity concentration in some plant species grown in rain forests of India to vary between 160.4 ± 12.3 and 206.4 ± 13.4 Bq kg -1 and TF value to vary between 0.802 and 0.954.…”
Section: K Activity Concentration Changes In Plants Treated With CD A...supporting
confidence: 62%
See 2 more Smart Citations
“…Potassium has an important role in photosynthesis, translocation of starches and sugars, plant-water relations, protein synthesis, activation of plant enzymes, resistance to plant diseases [8,29]. Similar results were reported in the studies examining the herbaceous and woody plants [7,15,27]. Manigandan et al [3] reported the 40K activity concentration in some plant species grown in rain forests of India to vary between 160.4 ± 12.3 and 206.4 ± 13.4 Bq kg -1 and TF value to vary between 0.802 and 0.954.…”
Section: K Activity Concentration Changes In Plants Treated With CD A...supporting
confidence: 62%
“…[32] analyzing 45 wheat flour samples reported 232Th activity concentration values that were much lower than in the present study. Similarly, Absar et al [27] reported the 232Th activity concentration of tea plant leaves to be 2.4 ±0.5-5.8 ±0.9 Bq kg -1 and that of soil to be 50±13-63±5 Bq kg -1 , whereas TF (232Th) was found to be 0.05±0.04. Bilgici Cengic & Çağlar [20] analyzed various herbs widely used in the Eastern Anatolian region and reported the 232Th activity concentration to be 55.99±4.32 Bq kg -1 and TF value to be 0.88.…”
Section: U Activity Concentration Changes and Tf Values In Plants Sub...mentioning
confidence: 87%
See 1 more Smart Citation
“…Van et al (2019) compared the Annual Committed Effective Dose Rate (ACED) of foodstuffs consumed by the people of Red River Delta in Vietnam to the ACED of other countries and concluded that the foodstuffs in Vietnam are safe for consumption because the ACEDs estimated for all the NORMs were found to be below the Global Limit of 1 mSv/yr. Absar et al (2021) examine tea leaves' naturally occurring radioactive elements using a Gamma-ray spectrometer.…”
Section: Determination Of Absorbed Dose Ratementioning
confidence: 99%
“…In some studies, the concentration of natural radioactivity and associated effective dose levels for 226 Ra, 232 Th, 40 K and 137 Cs radioisotopes were measured on agricultural lands, fertilizers and plant samples (grain crops, vegetables, medicinal plants and etc.) from different countries in the world (Al-Hamarneh et al, 2016;Bilgici Cengiz and Çağlar, 2019;Jibiri, and Fasae, 2012;Uchida and Tagami, 2007;Asaduzzaman et al, 2014;Absar et al, 2021;Bilgici Cengiz, 2019;Alfred et al, 2014).…”
Section: Introductionmentioning
confidence: 99%